1988
DOI: 10.1200/jco.1988.6.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with mastectomy or radiotherapy for stage III breast carcinoma: a Cancer and Leukemia Group B study.

Abstract: One hundred thirteen evaluable patients with previously untreated stage III breast carcinoma were treated with three monthly cycles of cyclophosphamide (CYC), doxorubicin (DOX), 5-fluorouracil (5-FU), vincristine (VCR), and prednisone (PRED) (CAFVP). Subsequently, 91 (81%) were deemed operable. Patients were then randomized to receive surgery or radiotherapy (RT) to determine which of these modalities afforded better local tumor control. All patients also received 2 additional years of CAFVP in a further attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(74 citation statements)
references
References 9 publications
2
65
0
7
Order By: Relevance
“…In our series as a whole (n = 69) the ACFuM treatment response rate was 61%, a figure in good accord with those of 65-72% obtained by others using doxorubicin containing chemotherapy regimens in stage 111-IV breast cancer patients (7,8).…”
Section: Discussionsupporting
confidence: 77%
“…In our series as a whole (n = 69) the ACFuM treatment response rate was 61%, a figure in good accord with those of 65-72% obtained by others using doxorubicin containing chemotherapy regimens in stage 111-IV breast cancer patients (7,8).…”
Section: Discussionsupporting
confidence: 77%
“…Touboul et al (29) reported that BCS is not inferior compared with mastectomy for the treatment of LABC after chemotherapy in regards to overall survival rates if residual tumor sizes were small. However, the optimal local management for patients with LABC remains undefined (14,(29)(30)(31). This warrant further study, particularly following recent advancements in systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…But approximately 10-20% of patients get complete clinical response and 50-60% achieves a partial response. [24][25][26][27][28][29][30] Thus it proves beyond doubt the role of Anthracycline combination schedule in Indian women in tumour response.…”
Section: Discussionmentioning
confidence: 99%